Sleep Hygiene Knowledge and Behavioral Evaluation of Sleep Problem in the Patients of a Health Promotion Hospital, Center 5, Nakhon Ratchasima - Intusorn, Kittichartd; Chiarakul, Supawadee; Lertkachatarn, Surang (Journal of Health Science of Thailand, 2017)
The survey studied behavior, knowledge evaluation of sleep hygiene among the patients visiting Regional Health Promotion Center 5 Nakhon Ratchasima by research questionnaires. Among 205 volunteers (female:male 2.5:1), they were 23-79 years old; 50.9, 10.8 year on average with high BMI (59.5%). It was found that 128 (62.4%) had sleep problems; 80 cases (39.0%) had initial insomnia, 90 cases (43.9%) had intermittent insomnia. While 66 cases (32.2%) had both initial and intermittent insomnia, some reported snoring (16.6%), sleep talking (3.4%) and hypersomnolance (2.4%). Sleep Hygiene Questionnaire analysis revealed 118 (57.6%) had irregular sleep time, 94 (45.9%), heavy meal before bedtime. Most (60.5%) remained tossing and turning even after 30 minutes in bed. In all, 136 cases had poor sleep environment, most (64.7%) of these problems were noise disturbances; 54 (26.3%) had frequently daytime naps. On sleep hygiene knowledge evaluation, most of them had good score (mean 14.3, 2.8 out of 18). Comparing between different subgroups, no statistically significant differences were found between education levels or economic status, but occupation group. Housewives and the unemployed had statistically significant higher score (15.0, 2.4) than farmers and merchants (p 0.044). Couple had higher score than single ones (p 0.048). Ignorance of effects of untimely alcohol and caffeine taking, tobacco smoking and heavy meal before bedtime were reported as well as how to avert insomnia. These vast gaps of knowledge dictate a need for more campaign on good sleep hygiene and behavioral change.